Analysis of Soil Base Cations Content after Application of Organic Fertilizer on Inceptisols at Lemon-Tree Orchard - Roby Nurdianto; Atiqah Aulia Hanuf; M. Wasilul Lutfi; Retno Suntari; Soemarno Soemarno (Agrotechnology Research Journal, 2024)
The lack of effectiveness of fertilization and the continuous use of inorganic fertilizers result in soil quality degradation. This research was conducted to analyses the effect of compost and manure on soil base saturation. This study used a simple Completely Randomized Design with 8 (eight) treatments and 4 (four) replications. The treatment consisted of P1 (topsoil); P2 (Subsoil); P3 (topsoil + compost); P4 (subsoil + compost); P5 (topsoil + cow manure); P6 (subsoil + cow manure); P7 (topsoil + goat manure); P8 (subsoil + goat manure). The results showed that the application of topsoil + compost significantly increased the exchangeable Ca content of the soil at 8 and 12 WAA (weeks after application). Application of goat manure on topsoil influenced increasing soil exchangeable Mg and exchangeable Na. The application of various organic materials has the effect of increasing the value of soil pH, CEC, and organic C content. The deep-placement fertilization technique is deemed effective in enhancing soil quality through chemical means, particularly by augmenting base cations and the soil's cation exchange capacity. This technology is pivotal in delivering nutrients directly to plant roots, thereby mitigating fertilizer losses caused by surface runoff and volatilization.